Functional paraganglioma. (20th February 2014) - Balasubramanian, Gokulakrishnan; Nellaiappan, Vallikantha
Abstract : Paraganglioma are tumours arising from neural crest cells of the sympathetic and parasympathetic paraganglia. Functional paraganglioma presents with symptoms of catecholamine excess that includes hypertension, flushing, diaphoresis, etc. Non-functional paraganglioma are usually found incidentally during imaging studies. Early diagnoses of functional paraganglioma are important because their removal is often curative. We present the case of a young man who presented with hypertensive crisis and severe headache, who was later found to have functional paraganglioma.